Assessment of Total Suspended Solid Concentration Dynamics Based on Geospatial Models as an Impact of Anthropogenic in Pekalongan Waters, Indonesia - Arij Kemala Yasmin Ridarto; Muhammad Zainuri; Muhammad Helmi; Kunarso Kunarso; Baskoro Baskoro; Lilik Maslukah; Hadi Endrawati; Gentur Handoyo; Magaly Koch (Universitas Diponegoro, 2023)
Changes in total suspended solids (TSS) concentrations provide information to determine the quality of the carrying capacity of waters as marine resources. This research aims to analyze the concentration and distribution of TSS in marine waters due to anthropogenic impacts on land. The concentration and distribution changes of TSS were analyzed using a geospatial model approach. The in-situ data were collected in August 2021 and June 2022 at 11 stations in the east monsoon and analyzed in the laboratory using the gravimetric method. The results show that TSS concentration changes at the study area significantly increased concentration from 40,3-85,4 mg/L in 2021 to 64,7-140,5 mg/L in 2022, increased by 37,6 – 39,2%, distributed to the east in open water due to the influence of the surface current, which is driven by the wind and tidal current. The anthropogenic factors, such as land use and micro-industrial activities, were dominantly correlated with the increase in TSS concentration in the waters, which is driven by input from land due to the influence of precipitation. This research provides comprehensive monitoring, evaluating, and managing scheme data and information to researchers, local governments, and environmentalists for mitigation planning to reduce the subtraction of water quality due to anthropogenic impacts.